ICT based communication channels preferences towards knowledge sharing among multicultural students - Ayu, Media Anugerah; Omari, Swaleh Maulid (IGI Global, 2012)
Many researches conducted in knowledge sharing have been focusing on organisational context. Yet, not many studies exist that explore knowledge sharing in education institutions. This paper provides an insight of how attitude, environment, motivation indicators, and individual factors (culture, age, and gender) would help in determining the preferences of information and communication technology (ICT) based communication channels among the students in multicultural institutions. The study uses quantitative design approach where data is collected from students studying in International Islamic University Malaysia (IIUM) Gombak Campus. The participants consisted of students originating from the regions of Middle East, West Africa, Southeast Asia and Eastern Europe. Information was solicited by the use of a survey. The survey was administered to a total of 184 participants. The research model designed for the study is based on the Theory of Planned Behaviour and Social Cognitive Theory. Factors involved in this study are attitude, environment, motivation, and demography, which includes cultural background. Six different communication channels have been looked through this study, i.e., instant messaging chat, social network, email, e-bulletin board, VOIP service, Telephone, and SMS. The results of the study can be used as a guide for identifying appropriate ICT based communication channels to be provided to the students for their knowledge sharing activities.